Ambulatory Gynecology (Springer New York, 2018)
There are approximately 55,000 practicing ob/gyns in the United States. The obstetrics and gynecology residency training authority (the Accreditation Council for Graduate Medical Education) has now pushed ambulatory primary and preventative care to the top of its list for residency training. Interest in the area of ambulatory gynecology is not just growing in the field of ob/gyn, however; family and primary care practitioners, emergency room physicians, and advance practice nurses all must know how to diagnose, manage, and treat gynecological conditions. Since office technology has expanded and decision-making has become increasingly complex, physicians need a guide through the endless list of treatment options for commonly presenting gynecologic disorders. Ambulatory Gynecology gives practitioners tools for diagnosis, investigation and management of these disorders, including decision-making algorithms. The text is evidence-based. From endocrine disorders to breast disease, preventative measures for osteoporosis to management of an abnormal pap smear, from adolescent gynecology to menopause, this book is crucial for office-based physicians to feel confident practicing in all areas of gynecology.